Platelet concentration in platelet concentrates and periodontal regeneration-unscrambling the ambiguity - A Suchetha; P Lakshmi; Divya Bhat; Darshan B Mundinamane; K V Soorya; G Ashit Bharwani (Wolters Kluwer Medknow Publications, 2015)
Context: Platelet-rich-plasma (PRP) and Platelet-rich-fibrin (PRF) are extensively used autologous platelet concentrates in periodontal regeneration, and PRF has a better efficacy as compared to PRP. The rationale for this difference has often been attributed to the difference in the structure of the fibrin matrix. However, the effect of concentration of platelets on the regenerative potential of these concentrates is obscure. Aims: The study was conducted to evaluate and compare, clinically and radiographically, the efficacy of PRF and PRP in the treatment of periodontal endosseous defects and to assess the effect of platelet concentration on periodontal regeneration. Materials and Methods: Twenty intrabony defects were selected and divided into two groups randomly by the coin toss method. Group I received PRP and Group II subjects were treated with PRF. The platelet counts in PRP and PRF were analyzed. Clinical and radiological parameters were assessed at baseline and 3, 6, and 9 months postoperatively. Statistical Analysis: Kruskal-Wallis Chi-square test, Wilcoxon signed rank test, t-test, and Spearman's rank correlation were used for statistical analysis of data. Results: There was statistically significant improvement in all the parameters in the two groups except in relation to gingival recession. There was a statistically significant difference between the platelet count in Group I and Group II (P = 0.002). Conclusion: PRP and PRF appear to have nearly comparable effects in terms of periodontal regeneration. The concentration of platelets appears to play a paradoxical role in regeneration. The regenerative potential of platelets appears to be optimal within a limited range.